(untitled) (Malay Literature, 2017)
Malay Patani authors who have migrated to Malaysia form their identities based on diasporic conditions. Most of their works focus on the genre of novels and short stories. Among the prominent authors is Isma Ae Mohamad who has produced many short stories. This paper aims to analyse the short stories of Isma Ae Mohamad by focusing on the cultural crisis and the search for identity faced by his characters. The short stories comprise "Cerita Dari Sempadan", "Ke Negeri Impian", "Perjalanan Ke Sebelah Sana", "Gadis Tomyam", and "Rindu Cerita Nenek". The diasporic author’s works are analysed based on the conceptual framework of diaspora studies proposed by Regina Lee. This study finds that the works of Isma Ae Mohamad fulfil the three proposed diaspora patterns, namely, the idealization of the homeland, manifestation of boutique multiculturalism, and identity politics in transition. In fact, his works also clearly illustrate the phenomena of cultural crisis and the search for identity. Various experiences of the diasporic community are expressed primarily on issues pertaining to education and citizenship. Overall, these short stories reflect the views of the diasporic community of Patani towards their past and the present of their lives. Findings of this study are important as the results can contribute towards the understanding of the fate of the diasporic Patanis and the crisis of identity that they face. Keywords: Malay Patani, diaspora, migration, search for identity